1984
DOI: 10.1152/ajpheart.1984.247.3.h478
|View full text |Cite
|
Sign up to set email alerts
|

Effects of myocardial contraction on ultrasonic backscatter before and after ischemia

Abstract: To determine whether contraction and relaxation influence quantitative myocardial ultrasonic backscatter we measured systolic and diastolic integrated backscatter separately in 10 pentobarbital-anesthetized dogs with defined, paced heart rates, before and after coronary occlusion. Data were acquired from intramural sites by coupling a broadband 5-MHz transducer to the left ventricular epicardium. Integrated backscatter was obtained from seven sequential ECG gated intervals throughout the cardiac cycle over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 0 publications
1
36
0
Order By: Relevance
“…20) In a pooled analysis of data from 11 published series, the sensitivity and specificity of dipyridamole scintigraphy for CAD detection averaged 85% and 90%, respectively. 23) Our study results were compatible with those reported in the literature.…”
Section: A B Discussionsupporting
confidence: 93%
“…20) In a pooled analysis of data from 11 published series, the sensitivity and specificity of dipyridamole scintigraphy for CAD detection averaged 85% and 90%, respectively. 23) Our study results were compatible with those reported in the literature.…”
Section: A B Discussionsupporting
confidence: 93%
“…This hypothesis is supported by several experimental studies, [18][19][20][21][22] wherein this parameter has been demonstrated to decrease with myocardial ischemia19,22 and infarction.21,22 As opposed to measurement of absolute IB, the variation in IB in humans is obtainable with a current system because it does not require any calibration of ultrasound signals and subsequent standardization among subjects. Thus, cardiac cycle-dependent variation of IB can be used to assess alterations in the acoustic properties of the myocardium even in humans.…”
Section: Discussionmentioning
confidence: 77%
“…In seven of the 13 patients with HCM, an intracavitary pressure gradient, assessed with continuous-wave Doppler echocardiography,28 was greater than 40 mm Hg at rest, and in the other five patients, a pressure gradient equal to or greater than 40 mm Hg was provoked by exercise or inhalation of amyl nitrate. One patient with systemic hypertension (19) was included in the group of HCM because the degree of hypertrophy was considered to be much greater than expected in patients having mild to moderate hypertension alone. Sixteen normal subjects (five men and 11 women), ranging in age from 37 to 62 years (mean, 49 years), served as controls.…”
Section: Patientsmentioning
confidence: 99%
“…Barzilai et al 28 have shown that 30 min after coronary artery occlusion there is considerable blunting of the diastolic-to-systolic variation in integrated backscatter. We have made similar observations using a two-dimensional approach ( figure 3, A).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a variable must be free of any angle dependence with respect to the region of interest and free from attenuation effects. An absolute measurement such as mean backscatter power, which has been used by several investigators, 22,23,28,29 has certain reference difficulties that potentially limit its clinical usefulness. On the other hand, relative measurements such as the cyclic backscatter power and the phase relationship may be useful in the clinical environment.…”
Section: Discussionmentioning
confidence: 99%